Evaluación del efecto de la labranza mínima y convencional en tres densidades en la producción de Caupí (Vigna Unguiculata (l.) walp), variedad blanco en la zona del Bajo Mayo - Shuña Bartra, René Armando (2013)
This paper titled "Evaluation of the effect of minimum tillage and conventional three densities in the production of cowpea (Vigna unguiculata (L.) Walp), White Variety in the Lower Mayo". This thesis work was carried out in the area of Miraflores Fundo belonging to the National University of San Martin - Tarapoto, which is located in the sector Ahuashiyacu, District Band Shilcayo, Province of San Martin, Peru. The effect on the agronomic and crop yield of Cowpea white densities in three systems under conditions of minimum tillage and conventional tillage. And economic analysis of profitability. This study was conducted from January 8, 2012 to April 7, 2012. We used the Randomized Complete Block Design (DBCR) factorial arrangement, 2 x 3 and 03 repetitions. In the meteorological data presents us with an average monthly average temperature of 25.8º C, with an average monthly total precipitation 198.1 mm and a relative humidity of 80%. The experimental soil shows a textural class of sandy loam with organic matter content of 2.84%, with a pH of 4.49. Before planting preparation was performed experimental area of each system are proposed as minimum tillage and conventional tillage. Planting was on January 8, 2012 with the use of a tacarpo to three inches deep, placed three seeds per hole; being used distancing planting each proposed treatments such as the T1 (0.50 x 0.25 m), T2 (0.60 x 0.25 m), T3 (0.70 x 0.25 m) with minimum tillage and T4 (0.50 x 0.25 m) T5 (0.60 x 0.25 m), T6 (0.70 x 0.25 m) with conventional tillage. The parameters studied were: emergence percentage (%), plant height (cm), days to flowering, pod size (cm), number of pods per plant, days to harvest, number of harvested plants, 100 seed weight (g) and yield per hectare. The results indicate that the plant height (cm), pod size (cm), number of pods per plant, 100 seed weight (g), were crucial to synchronize in higher yields per hectare obtained in treatments. Treatment T1 (LM + 0.50 m) obtained highest yield (926.59 kg ha-1) followed by T2 (LM + 0.60 m), T5 (LC + 0.60 m), T4 (LC + 0.50 m), T3 ( LM + 0.70 m) and T6 (LC + 0.70 m) who obtained yields of 901.69 kg ha-1, 784.60 kg ha-1, 784.29 kg ha-1, 730.17 kg ha-1 and 682.96 kg.ha -1, respectively. On the C/B and B/C shows that T2 (LM + 0.60 m) is economically more profitable, presenting a total cost of S /. 1708.80 news suns generating a utility value of S /. 455,256 news suns and a C/B of 3.75 and a B/C 0.27, followed by treatments T1 (LM + 0.50 m), T3 (LM + 0.70 m), T5 (LC + 0.60 m) and T4 (LC + 0.50 m) respectively, with net income of S/. 403,416, S/. 149,208, S/. -54.24 and S/. 34,104 respectively and a B/C of 0.22, 0.09, -0.03 and -0.02 respectively; finally T6 treatment (LC + 0.70 m) the latter being the largest deficit with its production cost S/.1771.20 soles generating a value utility of S /.132,096 news suns and a ratio C /B of -13.41 and a B /C -0.07.